2021
DOI: 10.2217/fon-2021-0225
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance and Function of MCM10 in Human Hepatocellular Carcinoma

Abstract: Aim: To investigate the role of MCM10, a conserved replication factor, in hepatocellular carcinoma (HCC). Methods: We used data from 364 HCC patients in the Cancer Genome Atlas database and conducted in vitro experiments to confirm the role of MCM10. Results: High MCM10 expression correlated with poor HCC patient outcome and was an independent prognosticator for HCC. Time-dependent receiver operating characteristic curve analysis found that the sequential trend of MCM10 for survival was not inferior to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For qRT-PCR, 2× SYBR Green qPCR Master Mix (EZBioscience) was used. The qRT-PCR reactions were performed on a CFX96 Touch Real-time PCR Detection System (Bio-Rad, CA, USA) ( 29 ). The following forward (F) and reverse (R) primers were used for amplification: IGFBP7, F 5'-CGA GCA AGG TCC TTC CAT AGT-3' and R 5'-GGT GTC GGG ATT CCG ATG AC-3'; and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), F 5'-GTC TCC TCT GAC TTC AAC AGC G-3' and R 5'-ACC ACC CTG TTG CTG TAG CCA A-3'.…”
Section: Methodsmentioning
confidence: 99%
“…For qRT-PCR, 2× SYBR Green qPCR Master Mix (EZBioscience) was used. The qRT-PCR reactions were performed on a CFX96 Touch Real-time PCR Detection System (Bio-Rad, CA, USA) ( 29 ). The following forward (F) and reverse (R) primers were used for amplification: IGFBP7, F 5'-CGA GCA AGG TCC TTC CAT AGT-3' and R 5'-GGT GTC GGG ATT CCG ATG AC-3'; and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), F 5'-GTC TCC TCT GAC TTC AAC AGC G-3' and R 5'-ACC ACC CTG TTG CTG TAG CCA A-3'.…”
Section: Methodsmentioning
confidence: 99%
“…[311][312][313] MCM9 and MCM10 are associated with additional tumor types such as colorectal cancer, breast cancer, ovarian cancer, and HCC (Table 3). [314][315][316][317][318][319][320][321][322] Compared with the common-used proliferation biomarker, MCM proteins are more sensitive and particular than PCNA and Ki-67, 323 accurately reflecting cell proliferation status and predicting prognostic tumor patient's survival rate.…”
Section: Mcms As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“… 311 , 312 , 313 MCM9 and MCM10 are associated with additional tumor types such as colorectal cancer, breast cancer, ovarian cancer, and HCC (Table 3 ). 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 …”
Section: Dna Replication Disease and Therapymentioning
confidence: 99%
“…In particular, high-throughput sequencing data can be used to identify key biomarkers associated with HCC progression, and these specific gene expression signature can effectively predict the risk and prognosis of HCC, providing new options for treatment. [6,7] For example, Chen et al found that high expression of MCM10 was associated with poor prognosis of patients with HCC and Medicine was an independent prognostic indicator for HCC [8] ; Ma et al showed that high expression of H2AFY predicted poor prognosis in HCC patients [9] ; Huo et al revealed that CTNNB1 mutations-related metabolic prognostic markers could be used in clinical practice to determine the prognosis of individual with HCC. [10] Taken together, biomarkers are relatively simple and noninvasive approach to detect and estimate disease prognosis, and will help physicians to better monitor patient outcomes and improve overall survival.…”
Section: Introductionmentioning
confidence: 99%